The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/nu11081865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moderate Chronic Food Restriction on the Development of Postprandial Dyslipidemia with Ageing

Abstract: Ageing is a major risk factor for the development of metabolic disorders linked to dyslipidemia, usually accompanied by increased adiposity. The goal of this work was to investigate whether avoiding an excessive increase in adiposity with ageing, via moderate chronic food restriction (FR), ameliorates postprandial dyslipidemia in a rat model of metabolic syndrome associated with ageing. Accordingly, we performed an oral lipid loading test (OLLT) in mature middle-aged (7 months) and middle-old-aged (24 months) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 59 publications
6
10
0
1
Order By: Relevance
“…Age-related fat gain is known to correlate with muscle and bone deterioration during OSO [35,46]. Moreover, it has been observed that body fat increases in Wistar rats throughout life, which has been related to a decrease in muscle mass, BMC, and life expectancy [57][58][59][60]. As mentioned before, one of the main benefits observed in the LIERLT routine was that reducing body fat increased the survival of Wistar female rats by 66%.…”
Section: Discussionmentioning
confidence: 84%
“…Age-related fat gain is known to correlate with muscle and bone deterioration during OSO [35,46]. Moreover, it has been observed that body fat increases in Wistar rats throughout life, which has been related to a decrease in muscle mass, BMC, and life expectancy [57][58][59][60]. As mentioned before, one of the main benefits observed in the LIERLT routine was that reducing body fat increased the survival of Wistar female rats by 66%.…”
Section: Discussionmentioning
confidence: 84%
“…On the contrary, insulinemia was increased in old rats following 36 h of fasting, according to their insulin-resistant state [15][16][17][18]. As previously reported [15][16][17][18], no differences were observed between 3-and 24month-old Wistar rats with respect to serum glucose and NEFA concentration after 16 or 36 h of fasting. NEFA concentrations decreased to a similar extent in both groups of rats after 36 h of fasting.…”
Section: Effect Of Fasting or Fasting/refeeding On Metabolic Characteristics Of Young And Old Wistar Ratsmentioning
confidence: 77%
“…Thus, the 24-month-old rats used in the present study were middle-old age animals. These old rats were not at high risk of mortality and did not present apparent signs of frailty [15][16][17]36], although they showed higher intracellular accumulation of lipofuscin, compared to 3-month-old Wistar rats [17], a marker of cellular senescence.…”
Section: Animals and Ethic Statementsmentioning
confidence: 99%
See 2 more Smart Citations